Residence Time in Hyporheic Bioactive Layers Explains Nitrate Uptake in Streams. Issue 2 (17th February 2021) - Li, Angang; Bernal, Susana; Kohler, Brady; Thomas, Steven A.; Martí, Eugènia; Packman, Aaron I.
Abstract: The Tracer Additions for Spiraling Curve Characterization (TASCC) model has been rapidly adopted to interpret in‐stream nutrient spiraling metrics over a range of concentrations from breakthrough curves (BTCs) obtained during pulse solute injection experiments. TASCC analyses often identify hysteresis in the relationship between spiraling metrics and concentration as nutrient concentration in BTCs rises and falls. The mechanisms behind these hysteresis patterns have yet to be determined. We hypothesized that differences in the time a solute is exposed to bioactive environments (i.e., biophysical opportunity) between the rising and falling limbs of BTCs causes hysteresis in TASCCs. We tested this hypothesis using nitrate data from Elkhorn Creek (CO, USA) combined with a process‐based particle‐tracking model representing travel times and transformations along each flow path in the water column and hyporheic zone, from which the bioactive zone comprised only a thin superficial layer. In‐stream nitrate uptake was controlled by hyporheic exchange and the cumulative time nitrate spend in the bioactive layer. This bioactive residence time generally increased from the rising to the falling limb of the BTC, systematically generating hysteresis in the TASCC curves. Hysteresis decreased when nutrient uptake primarily occurred in the water column compared to the hyporheic zone, and with increasing the distance between the injection and sampling points. Hysteresis increased with the depth of the hyporheic bioactive layer. Our results emphasize that good characterization of spatial heterogeneity of surface‐subsurface flow paths and bioactive hot spots within streams is essential to understanding the mechanisms of in‐stream nutrient uptake. Plain Language Summary: Human activities negatively impact water quality by supplying excessive nutrients to streams. To investigate the capacity of streams to take up nutrients from the water column, scientists usually add nutrients to stream reaches, calculate the fraction of added nutrients that is taken up, and identify the environmental conditions controlling nutrient uptake. A common idea is that nutrient uptake increases with increasing water residence time because of increased contact time between solutes and organisms. Yet, water residence time only partially explains the temporal and spatial variability of nutrient uptake, and the reasons behind this variability are still not well understood. We use a mathematical model to test a simple idea: the organisms responsible for the uptake of nitrate, a major form of dissolved nitrogen, are confined within a thin layer in the stream sediments. We define the time spent within this bioactive layer as the "bioactive residence time." Greater bioactive residence time for nitrate corresponds with higher nitrate uptake along the whole reach. Our model successfully reproduces nitrate uptake patterns observed during nitrate addition experiments, suggesting that bioactive residence time is important for nutrient uptake. Our study sheds new light on how streams can improve water quality by decreasing nutrient loads. Key Points: Residence time in the hyporheic bioactive zone is a key control on nitrate uptake in streams Spatial variability of hyporheic flow and biological activity creates different biophysical opportunities for nitrate removal during downstream transport Hysteresis in TASCC curves emerges when biophysical opportunity increases from the rising to the falling limb of the breakthrough curve